Health Risks Management Program in Schools: An Operational Study in Türkiye - Atak, Muhammed; Önal, Ayşe Emel; Şimşek, Zeynep; İşsever, Halim (MDPI, 2023)
This study was carried out to improve the quality of school health services with the operational epidemiology method. The study aimed to describe the current status of the School Health Protection and Improvement Program (SHPIP), the difficulties experienced during its implementation, to develop evidence-based solution methods, and to test the proposed solutions, in a district with a population of 400,513, 20.4% of which is of school age between the ages of 5–19. The “Health Risk Management Program at Schools”, which consists of the stages of putting the results into practice by sharing the results with the relevant parties, wasdeveloped. In this study, a cross-sectional research design was employed using questionnaire forms, while qualitative data were collected through the use of the phenomenological analysis method, specifically through the conduct of focus group interviews. SHPIP year-end evaluation forms of 191 schools were reviewed retrospectively, questionnaires were applied to 554 school staff and 146 family health center staff between 21 October 2019 and 21 November 2019 using the probabilistic sampling (simple random) method, and semi-structured focus group interviews were conducted with 10 school health study executives. The most common health risks in schools and the risks identified during the execution of school health services were identified. In order to eliminate the lack of in-service training, training modules for “School Health Management Teams” were developed and impact analyses were conducted. After the intervention, a significant difference was found in the compliance of schools with SHPIP, and the application of all components of the school health program increased from 10.0% to 65.6% (p < 0.05). The program has been integrated into the “School Health Protection and Improvement Program” (SHPIP) with the decisions of the District School Health Board and District Hygiene Council. © 2023 by the authors.
Keywords: children and adolescent; intervention; management of health risks; operational epidemiology; school health